2022
DOI: 10.1371/journal.pgph.0000282
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and self-harm in low- and middle- income countries during the COVID-19 pandemic: A systematic review

Abstract: There is widespread concern over the potential impact of the COVID-19 pandemic on suicide and self-harm globally, particularly in low- and middle-income countries (LMIC) where the burden of these behaviours is greatest. We synthesised the evidence from the published literature on the impact of the pandemic on suicide and self-harm in LMIC. This review is nested within a living systematic review (PROSPERO ID CRD42020183326) that continuously identifies published evidence (all languages) through a comprehensive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
1
15
0
2
Order By: Relevance
“…Despite concerns, available data internationally suggest that there has been no increase in the rates of suicide during the pandemic, and our findings from Sri Lanka are in keeping with this [3,6]. During the pandemic period of 2019-2021, admissions for self-poisoning showed an overall decreasing pattern, with temporary step reductions during the periods of lockdown.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Despite concerns, available data internationally suggest that there has been no increase in the rates of suicide during the pandemic, and our findings from Sri Lanka are in keeping with this [3,6]. During the pandemic period of 2019-2021, admissions for self-poisoning showed an overall decreasing pattern, with temporary step reductions during the periods of lockdown.…”
Section: Discussionsupporting
confidence: 78%
“…This is one of the very few studies investigating the impact of the pandemic on suicide and self-harm in populations living in LMICs [6] and presented data on both self-harm and suicide. It includes data from several years and is able, therefore, to model underlying trends.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few primary studies found an overall increase in the prevalence of suicidal ideation and attempts, and in the rate of death by suicide during the pandemic period compared with the pre-pandemic period [ 8 , 9 , 10 ], while other studies found a decreased trend [ 11 , 12 , 13 ], and some reported an overall stable trend [ 14 , 15 , 16 ]. Suicide studies during the pandemic tend to be methodologically poor [ 17 ], and high-quality evidence from an interrupted time-series study covering 33 countries showed no significant increases in suicide death in most countries/regions [ 18 ]. After synthesizing three studies, Prati et al [ 19 ] found that the effect of the COVID-19 lockdown on suicide risk among the general population was not significant.…”
Section: Introductionmentioning
confidence: 99%
“…There was evidence of trend line differences between the two periods when the increase in contact rate was compared. Other mental health services in the UK showed a reduction of service utilization during the pandemic too, along with a stable number of admissions before and during Covid-19 35,36 . One possible explanation for the change in user behaviour in digital service is that the need for support from young people peaks at the start of the pandemic.…”
Section: Changes In Service Access and Activitymentioning
confidence: 98%